Parámetros cardiológicos en caninos domésticos sanos asociados a sexo, edad y talla (Veterinary Science, 2025)
The objective was to describe cardiological parameters in healthy canines and associate them with constitutive variables (age, sex and size). 178 animals were selected, age range 6.5 ±3.7 years, 81 males and 97 females, average weight 19.8 kg ±11.3 and average body condition 2.9 ±0.3. The sample was divided into 12 groups according to age (< 8 and > 8 years), sex (males and females) and size (< 12 kg, between 12 kg and 25 kg and > 25 kg). Systolic blood pressure (SBP), electrocardiographic, radiological and echocardiographic evaluation were determined in each canine. PAS had a mean of 146 mmHg ±20 mmHg, with no differences associated with sex/age/height. There were differences, for height, in P wave time and R deflection amplitude, the group < 12 kg presented 0.04 sec and 1.9 mv, between 12-25 kg 0.046 sec and 2.4 mv and > 25 kg 0.052 sec and 3.0 mv, respectively. The vertebral heart score (VHS) was 9.7 ±0.6, minimum 8.0 and maximum 11.2. The > 25 kg group showed higher VHS than other groups, with average values ​​greater than 10. The shortening, thickening and ejection fraction were 33% ±6%, 31% ±8% and 56% ±8%, respectively. No differences were evident in association with sex/age/height. The separation distance from point E to the septum had a maximum value of 7.1 mm; with gradual increase in relation to weight. The aorta/left atrium ratio had a mean of 1.06 ±0.12, with a maximum value of 1.26, showing no differences in relation to sex/age/height.